Real Exchange Rates and the Prices of Nontradable Goods - Micossi, S. (IMF Working Papers; Working Paper, 1994)
This paper attempts to provide a perspective on real exchange rate developments following the inception of the EMS. The focus is on structural determinants of real exchange rates, notably the behavior of tradables and nontradable prices and productivity. It is found that changes in the relative price of tradable goods in terms of nontradables account for a sizable fraction of real exchange rate dynamics during the EMS period. Sectoral productivity growth differential help explain the behavior of the relative price of tradable goods, especially in the long run. There is also some evidence that the EMS has extended on relative price behavior.